MOTILITY AND CEMENT VIABILITY FRESH ETAWA COPPER (ELEVATOR) USING EPIDIDYMAL PLASMA CAUDER CASTER (CEP-2) ON LONG AND DIFFERENT TIME SAVE - Philipus Pati Pelang Sekosi; Enike Dwi Kusumawati; Aju Tjatur Nugroho Krisnaningsih (Jurnal Sains Peternakan, 2016)
The purpose of this research is to knowing the fresh sperm PE goat motility using a CEP-2 diluent in different time and temperature storage. The methods is a research laboratory with temperature treatment (5°C and 24°C) as well as the time storage (0, 1, 2, 3, 4, 5, 6) hour using a complete Randomized Factorial Design each treatment consist of 10 repeats. Based on the result of this study showed that PE goat spermatozoa motility using a CEP-2 diluent in temperature and different time storage there is a very significanly influence (P